[SPS Conference on traineeship - 9 July 2010] - Psychiatrically ill individuals and the demand for psychotherapy in the Mental Health Services. - Carli, Renzo (Rivista di Psicologia Clinica, 2011)
This was the introductory talk at the Conference held in July 2010 “The clients of the Mental Health Services” sponsored by the School of Specialisation in Psychoanalytical Psychotherapy run by Studio di Psicosociologia, Rome. An analysis is made of the Mental Health Services and the possible relational dynamics in the health services and in the facilities where the trainees carry out the practical traineeships for their specialisation. Establishing a relation between the staff and so-called psychiatrically ill patients entails a series of problems. Some of these are dealt with here, based on the reporting of practical traineeship experiences. The staff-member, in these cases, is seen as a thinking support for the emotions of the mentally ill individual, an integrative role that can give a sense to the patient’s emotions and translate them into a coherent and communicable continuum. Another aspect dealt with is the evolution of the relationship, inside the services, between demand and supply in Mental Health Centers which, especially since the Nineties, has not been connected only to mental illness. In recent years the psychotherapeutic service has been accompanied by pharmacological intervention and rehabilitation initiatives for the return to society. This paper examines the phenomenon in depth and suggests categories and critera of interpretation and intervention.